Hans Brøchners forelæsninger om Kierkegaard - Koch, Carl Henrik (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
Philosopher Hans Brøchner (1820-1875) was a distant relative of Søren Kierkegaard (1813-1855) and was the person among his contemporaries who wrote what were probably the most well-known and comprehensive memoirs about him. Although their views of Christianity and philosophy were diametrically opposed, the younger author studied the older author’s works and was the first to present an overall exposition of Kierkegaard’s opus. Brøchner was appointed extraordinary lecturer in philosophy in 1857 and, as early as 1858-59, held the first lectures on Kierkegaard at the University of Copenhagen in which he faithfully and respectfully, but also critically, reviewed Kierkegaard’s works. He repeated this criticism in his contribution to the battle on faith and knowledge in the mid 1860s.